The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1136/postgradmedj-2020-139133
|View full text |Cite
|
Sign up to set email alerts
|

Rapid exponential increase in neurosurgery departmental scholarly output following an intensive research initiative

Abstract: There has been extensive research into methods of increasing academic departmental scholarly activity (DSA) through targeted interventions. Residency programmes are responsible for ensuring sufficient scholarly opportunities for residents. We sought to discover the outcomes of an intensive research initiative (IRI) on DSA in our department in a short-time interval. IRI was implemented, consisting of multiple interventions, to rapidly produce an increase in DSA through resident/medical student faculty engagemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Our IRI resulted in a 350% increase in medical student and 4900% increase in PRF scholarly activity and this is the most rapid report of successful exponential departmental scholarly activity growth reported in the literature to date. 7 Though long-term IRI follow-up is warranted, we show our research initiative has now been effective and reproducible in two different institutions, both with, and without, a neurological surgery residency training program. Institutions committed to successful medical student mentorship must find ways to get students opportunities for rich academic productivity and the IRI can provide a framework for motivated faculty and learners to rapidly increase departmental scholarly activity.…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…Our IRI resulted in a 350% increase in medical student and 4900% increase in PRF scholarly activity and this is the most rapid report of successful exponential departmental scholarly activity growth reported in the literature to date. 7 Though long-term IRI follow-up is warranted, we show our research initiative has now been effective and reproducible in two different institutions, both with, and without, a neurological surgery residency training program. Institutions committed to successful medical student mentorship must find ways to get students opportunities for rich academic productivity and the IRI can provide a framework for motivated faculty and learners to rapidly increase departmental scholarly activity.…”
Section: Discussionmentioning
confidence: 79%
“…We previously reported our 2-year intensive research initiative (IRI) experience that rapidly increased departmental scholarly activity within a neurological surgery residency training program by focusing on resident and medical student mentorship. 7 That study demonstrated how departments could rapidly obtain exponential increases in their departmental scholarly activity, satisfying the residency requirement of providing an environment of scholarly activity and research. There were no previous guidelines, so we summarized the limited literature from other specialties, and shared our IRI experience to offer a possible solution for departments that needed rapid increases in academic productivity.…”
Section: Methodsmentioning
confidence: 92%
See 3 more Smart Citations